Mucocutaneous junctional and flexural paresthesias caused by the holoplanktonic trachymedusa Liriope tetraphylla - Mianzan, Hermes Walter (2000)
Multiple stages of Liriope tetraphylla caused paresthesias leading to chafing and excoriations in swimmers along the Southern Uruguayan and Northern Argentinean Atlantic coasts. These episodes appear seasonally in the summer and affect groups of bathers in shallow water (1-3 m). Copyright (C) 2000 S. Karger AG, Basel.